Esophageal stenting for benign and malignant disease: European Society of Gastrointestinal Endoscopy (ESGE) Guideline – Update 2021 - Spaander, Manon C. W.; van der Bogt, Ruben D.; Baron, Todd H.; Albers, David; Blero, Daniel; de Ceglie, Antonella; Conio, Massimo; Czakó, László; Everett, Simon; Garcia-Pagán, Juan-Carlos; Ginès, Angels; Jovani, Manol; Repici, Alessandro; Rodrigues-Pinto, Eduardo; Siersema, Peter D.; Fuccio, Lorenzo; van Hooft, Jeanin E. (Endoscopy, 2021)
Malignant disease1 ESGE recommends placement of partially or fully covered self-expandable metal stents (SEMSs) for palliation of malignant dysphagia over laser therapy, photodynamic therapy, and esophageal bypass.Strong recommendation, high quality evidence.2 ESGE recommends brachytherapy as a valid alternative, alone or in addition to stenting, in esophageal cancer patients with malignant dysphagia and expected longer life expectancy.Strong recommendation, high quality evidence.3 ESGE recommends esophageal SEMS placement for sealing malignant tracheoesophageal or bronchoesophageal fistulas. Strong recommendation, low quality evidence.4 ESGE does not recommend SEMS placement as a bridge to surgery or before preoperative chemoradiotherapy because it is associated with a high incidence of adverse events. Other options such as feeding tube placement are preferable. Strong recommendation, low quality evidence.Benign disease5 ESGE recommends against the use of SEMSs as first-line therapy for the management of benign esophageal strictures because of the potential for adverse events, the availability of alternative therapies, and their cost. Strong recommendation, low quality evidence.6 ESGE suggests consideration of temporary placement of self-expandable stents for refractory benign esophageal strictures. Weak recommendation, moderate quality evidence.7 ESGE suggests that fully covered SEMSs be preferred over partially covered SEMSs for the treatment of refractory benign esophageal strictures because of their very low risk of embedment and ease of removability. Weak recommendation, low quality evidence.8 ESGE recommends the stent-in-stent technique to remove partially covered SEMSs that are embedded in the esophageal wall. Strong recommendation, low quality evidence.9 ESGE recommends that temporary stent placement can be considered for the treatment of leaks, fistulas, and perforations. No specific type of stent can be recommended, and the duration of stenting should be individualized. Strong recommendation, low quality of evidence.10 ESGE recommends considering placement of a fully covered large-diameter SEMS for the treatment of esophageal variceal bleeding refractory to medical, endoscopic, and/or radiological therapy, or as initial therapy for patients with massive bleeding. Strong recommendation, moderate quality evidence.